Noninvasive Prenatal Diagnosis of Fetal RHD Status Using Cell-free Fetal DNA in Maternal Plasma - MH Ahmadi; AA Pourfathollah; M Rabiee; N Amirizadeh (JRI, 2022)
Background: The main cause of hemolytic disease of the fetus and newborn (HDFN) is the incompatibility of the RHD antigen between mother and fetus. Following the discovery of cell-free fetal DNA (cffDNA), noninvasive fetal RHD genotyping also became possible, which will help in the better management of immunized RHD negative mothers and in the targeted prenatal injection of Rho(D) immune globulin (RhIG). The objective of this study was to establish a reliable method with high accuracy to determine the fetal RHD genotype. Methods: The project was a prospective observational cohort study. After cell-free DNA (cfDNA) extraction from maternal plasma, fetal RHD genotyping was performed by duplex real-time polymerase chain reaction (PCR) and exons 5, 7, and 10 of the RHD gene were examined. SRY and RASSF1A genes were used as internal controls to confirm the presence of cffDNA in maternal plasma. Results: Out of 40 samples, 33 were RhD positive heterozygous mothers and 7 cases were RHD negative. In three cases where both the fetal RHD and SRY genotypes were negative, RASSF1A was amplified in cell-free DNA sample treated with the BstUI enzyme, and the presence of cffDNA was confirmed. Conclusion: The findings reveal that the strategy used in this study is reliable and it is possible to determine the fetal RHD status with high accuracy. The strategy can help targeted injection of RhIG and prevent unnecessary injection in RhD negative mothers who carry an RhD negative fetus.